2014
DOI: 10.1590/1808-1657001192012
|View full text |Cite
|
Sign up to set email alerts
|

Comparação de métodos para avaliação da atividade antimicrobiana e determinação da concentração inibitória mínima (cim) de extratos vegetais aquosos e etanólicos

Abstract: Several studies have been conducted to discover new antimicrobial agents from plants to be used in pharmaceuticals, cosmetics and in the food industry. The lack of standardized methods for the evaluation of plant extracts with antimicrobial potential complicates the comparison of results. Taking into consideration the need to establish a method with consistent results to evaluate the antimicrobial activity of plant extracts, this study aimed to evaluate the antimicrobial activity of extracts of some plants fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
40

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 14 publications
2
41
1
40
Order By: Relevance
“…Last, total extract and bioactive fractions bactericidal or bacteriostatic effects are exemplified in Table 3. Some authors report this effect as minimum bactericidal concentration (MBC) [64,66,113]. In contrast to disk diffusion method, we observed that Berberis goudotii total extract presented anticariogenic activity against Streptococcus mutans with concentrations of 25 and 50 µg/µL with an RPI of 36.2 ± 5.7 and 51.2 ± 6.3% respectively.…”
Section: Anticariogenic and Antiperiodontal Activitiescontrasting
confidence: 56%
“…Last, total extract and bioactive fractions bactericidal or bacteriostatic effects are exemplified in Table 3. Some authors report this effect as minimum bactericidal concentration (MBC) [64,66,113]. In contrast to disk diffusion method, we observed that Berberis goudotii total extract presented anticariogenic activity against Streptococcus mutans with concentrations of 25 and 50 µg/µL with an RPI of 36.2 ± 5.7 and 51.2 ± 6.3% respectively.…”
Section: Anticariogenic and Antiperiodontal Activitiescontrasting
confidence: 56%
“…Atividade Antioxidante A avaliação da atividade antioxidante dos extratos de E. anomala e P. salutare foi procedida conforme metodologia adaptada da desenvolvida por Brand- Williams et al (1995), a qual baseia-se na redução do radical livre difenil-picril-hidrazina (DPPH) na presença de substâncias antioxidantes que pode ser observada pelo decréscimo da absorbância e visualizada pela alteração da coloração da solução de púrpura para amarelo.…”
Section: Resultsunclassified
“…A atividade antioxidante foi determinada através da avaliação da redução do radical DPPH por espectrofotometria conforme a metodologia adaptada desenvolvida por Brand- Williams et al (1995) Foram preparadas soluções estoque dos extratos na concentração de 20.000 µg/mL diluídos em dimetilsufóxido (DMSO) 0,5% e água purificada estéril. Como padrão antimicrobiano foi empregado o cloranfenicol 0,2 µg/µL e como controle do diluente foi utilizado uma solução de DMSO 0,5%.…”
Section: Atividade Antioxidanteunclassified
“…As regards Gram-positive bacteria, several studies demonstrate the antibacterial activity of natural products of the species from the Psidium genus, indicating activity against S. aureus, and also against several other strains, among them Staphylococcus epidermidis, Bacillus subtilis, Bacillus cereus, Proteus mirabilis, Streptococcus pyogenes, Streptococcus mutans, Streptococcus salivarius, Streptococcus oralis, Lactobacillus rhamnosus, Salmonella enteritidis (GONÇALVES, ALVES FILHO;MENEZES., 2005;SANCHES et al, 2005;NAIR;CHANDA, 2007;MEDINA et al, 2011;SILVA et al, 2013;BONA et al, 2014;SCUR et al, 2014;JARDIM et al, 2015;ALVARENDA et al, 2015;SILVA et al, 2016).…”
Section: Antimicrobial Activitymentioning
confidence: 99%